Burkholderia gut symbiont induces insect host fecundity by modulating Kr‐h1 gene expression. Issue 2 (30th November 2022) - Lee, Junbeom; Lee, Dae‐Weon
Abstract: Full‐length cDNAs of the Broad‐Complex (BR‐C) from Riptortus pedestris were cloned. Moreover, Kr‐h1 and BR‐C expression levels in apo‐symbiotic and symbiotic host insects were compared to verify whether they are modulated by Burkholderia gut symbionts. Interestingly, Kr‐h1 expression level was significantly increased in symbiotic females. To determine how Kr‐h1 affects fecundity in insects, the biosynthesis of two reproduction‐associated proteins, hexamerin‐α and vitellogenin, was investigated in R. pedestris females. Hexamerin‐α and vitellogenin expression at the transcriptional and translational levels decreased in Kr‐h1 ‐suppressed symbiotic females, subsequently reduced egg production. These results suggest that Burkholderia gut symbiont modulates Kr‐h1 expression to enhance ovarian development and egg production of R. pedestris by increasing the biosynthesis of the two proteins. Abstract : A putative linkage between gut symbionts and host fitness. Juvenile hormone (JH) in the insect brain is induced upon colonization with the Burkholderia gut symbiont, leading to the regulation of two endocrine proteins, Kr‐h1 and BR‐C. The expression of these endocrine proteins affects host fitness, development, and egg production. The red arrow lines indicate the results described in previous studies, and the blue arrow dashed lines indicate putative links in this study.